Assessment of awareness and behaviour among secondary school students on climate change - Abd Hamid @ Ghazali, Izzah; Wan Yahaya, Wan Asrina; Rahim, Hairazi (Secholian Publication, 2021)
The climate change issue has been recognised as a global problem and it has to be given serious attention. The human contribution is necessary, it can be done through spreading awareness that will lead to behavioural changes. This study aims to assess the awareness and behaviour of secondary students and their contribution towards preventing climate change. The study was conducted with Nature Lovers and Peer Counsellors Club members at SMK Bandar Bintulu. About 133 surveys using Likert-scale with rating 1 to 4 were collected and analysed on frequency and percentage by SPSS. Findings revealed that the respondents’ awareness of climate change occurs as they learn from the classroom and join the environmental related club. However, their awareness does not represent their behaviour in protecting climate change due to minimum exposure on the human contribution towards climate change. Therefore, this study, suggests a long-term campaign related to the effects of climate change on health, including proper education on rules and regulation implemented by authorities to cater for this situation.